The Use of Nanoadditives Within Recycled Polymers for Food Packaging: Properties, Recyclability, and Safety - Guarda-Moraga, A; Galotto-Lopez, M; Rojas-Sepulveda, A; Lopez de Dicastillo-Bergamo, A; Velasquez, E (Blackwell Publishing Inc., 2020)
Nanotechnology is considered a highly valued technology to reduce the current environmental problem that is derived from plastic accumulation. The need to recycle and reuse packaging materials is essential to create a sustainable society towards a circular economy. However, the reprocessing of polymers leads to the deterioration of their characteristic mechanical, optical, thermal, and barrier properties due to the degradation of their polymeric chains. When recycled polymers are reinforced with nanoadditives, aforementioned properties improve and their use in the circular economy is more viable. In this review, different types of nanoadditives and recent advances in the development of recycled polymer nanocomposites reinforced with nanoadditives will be presented. In addition, there is a description of two research topics of current interest, recyclability of nanocomposites and safety for food packaging applications. Recyclability of nanocomposites requires a study that includes the nature of the polymer matrix, the type of polymer and the concentration of nanofiller, the morphology, the presence of additives, and the conditions of the thermal-mechanical cycles. Finally, safety section is dedicated to clarify the migration process in nanoreinforced-recycled polymers in order to assess their safety for food contact applications. © 2020 Institute of Food Technologists®